2021
DOI: 10.1002/ppsc.202000328
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Reinforced Anisometric Patchy Supraparticles for Self‐Propulsion

Abstract: The preparation of fumed silica‐based anisometric supraparticles with well‐defined catalytically active patches suitable for self‐propulsion is presented here. These sub‐millimeter‐sized particles can self‐propel as they contain Pt‐covered magnetite (Fe3O4) nanoparticles, where the Pt can decompose catalytically a “fuel” like H2O2 and thereby propel the supraparticles. By their magnetic properties, the catalytically active nanoparticles can be concentrated in patches on the supraparticle surface. The goal is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…Multiple types of materials, ranging from nanometer-sized quantum dots or metal organic frameworks to micrometer-sized polystyrene (PS) particles, with different shapes and chemistries can be used as building blocks to create supraparticles. The supraparticles may have emergent properties that surpass the mere sum of their parts, arising from the interactions between different types of building blocks. , Therefore, supraparticles are versatile materials with potential applications in many fields of science and technology, including catalysis, , gas adsorption and sensing, , drug encapsulation and delivery, , photonics, and energy production and storage. , …”
Section: Introductionmentioning
confidence: 99%
“…Multiple types of materials, ranging from nanometer-sized quantum dots or metal organic frameworks to micrometer-sized polystyrene (PS) particles, with different shapes and chemistries can be used as building blocks to create supraparticles. The supraparticles may have emergent properties that surpass the mere sum of their parts, arising from the interactions between different types of building blocks. , Therefore, supraparticles are versatile materials with potential applications in many fields of science and technology, including catalysis, , gas adsorption and sensing, , drug encapsulation and delivery, , photonics, and energy production and storage. , …”
Section: Introductionmentioning
confidence: 99%
“…It was stated that the well-defining of the resulting patchy will change the propulsion properties of the particles. CMXRF enabled the 3D investigation of the internal structure and distribution of the nanoparticles with a resolution of about 30 µm [ 64 ].…”
Section: Applications Of Cmxrf Spectroscopymentioning
confidence: 99%
“…Oguzturk et al 22 reported on the preparation of fumed silica-based anisometric supraparticles with catalytically active Pt-covered magnetite (Fe 3 O 4 /Pt) patches, suitable for self-propulsion. Use of confocal μXRF spectrometry made it possible to locate the catalytic Fe 3 O 4 /Pt NPs precisely within the mm-sized supraparticles with a resolution in the μm range and thereby provide detailed internal structural information on various supraparticles.…”
Section: Chemical Imaging Using X-ray Techniquesmentioning
confidence: 99%